Television and the Cultivation of Authoritarianism: A Return Visit From an Unexpected Friend. (8th May 2017) - Morgan, Michael; Shanahan, James
Abstract : The 2016 Presidential election brought a surprise: the rise of Donald Trump as a viable candidate for the Republican nomination. What started as a seeming publicity stunt morphed into something more. Trump raised fears of authoritarianism—and even fascism—that were thought to be mostly confined to other countries. This study uses a national sample to examine television viewing's relationship to authoritarian values. We find that heavy viewers of television are more likely to be authoritarian, and that authoritarians are more likely to support Trump. We find an indirect relationship between amount of viewing and Trump support through authoritarianism. These findings have implications for current political debates as well as for media effects theory.